1970
DOI: 10.1172/jci106438
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation of albumin but not fibrinogen synthesis by corticosteroids in patients with hepatocellular disease

Abstract: A B S T R A C T Simultaneous studies of albumin and fibrinogen metabolism have been conducted using the carbonate-14C method before and after a 13 day course of prednisolone in eight patients with hepatocellular disease. Initially six patients were hypoalbuminemic. The mean plasma albumin and fibrinogen concentrations and albumin and fibrinogen synthetic rates were all lower than the corresponding values in a group of control subjects. Prednisolone therapy was associated with significant increases in the plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
1

Year Published

1973
1973
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(17 citation statements)
references
References 16 publications
3
13
1
Order By: Relevance
“…The increase observed in the present study was clearly larger and corresponds to the maximum turnover rates of labelled albumin found by Martini et al (8) in patients with protein-losing enteropathy. Our results differ considerably from those obtained by Wochner et al (16) who observed a 25 % increase of albumin synthesis in patients with protein-losing enteropathy and a mean albumin synthesis rate of 140 mg/kg/day in control patients which is a rather low figure in comparison with data by other authors (1,9,10,(13)(14)(15). This difference might be due to the fact that Wochner et al (16) used urine instead of plasma for the determination of urea SA although this modification was found equivalent to the original method by other authors (10) but in their hands tended to give somewhat higher values than the original method.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The increase observed in the present study was clearly larger and corresponds to the maximum turnover rates of labelled albumin found by Martini et al (8) in patients with protein-losing enteropathy. Our results differ considerably from those obtained by Wochner et al (16) who observed a 25 % increase of albumin synthesis in patients with protein-losing enteropathy and a mean albumin synthesis rate of 140 mg/kg/day in control patients which is a rather low figure in comparison with data by other authors (1,9,10,(13)(14)(15). This difference might be due to the fact that Wochner et al (16) used urine instead of plasma for the determination of urea SA although this modification was found equivalent to the original method by other authors (10) but in their hands tended to give somewhat higher values than the original method.…”
Section: Discussioncontrasting
confidence: 99%
“…Using data con cerning the time course of the intracellular transport of newly synthesized albumin (2), Rothschild et al (13) calculated that under normal conditions the liver works at about 30% of its albumin synthetic capacity. Patients with inactive liver cirrhosis, in spite of a considerable loss of functioning liver tissue, tend to have normal or augmented albumin synthesis rates (13), which may be even further increased by steroids (1). This indicates a substantial rise in albumin synthesis rate in the remaining tissue.…”
mentioning
confidence: 99%
“…If the immune response to either native or altered self antigens results in the hepatocellular dysfunction (Meyer zum Buschenfelde and Hopf, 1974), this would be reduced and thus hepatocellular destruction decreased. Corticosteroids also stimulate protein synthesis (Cain et al, 1970;Rothschild et al, 1975) and this may contribute to the beneficial response. Reduced liver cell destruction and enhanced hepatic protein synthesis may lead to the increased plasma albumin seen during the early period of the study.…”
Section: Discussionmentioning
confidence: 99%
“…99 Fibrinogen production has been shown to increase in response to glucocorticoids both in vitro'00-102 and in vivo. 103,104 The natural defence to fibrin deposition and clot formation is the fibrinolytic system, initiated by tissue plasminogen activator. Although there are no studies of the overall changes in fibrinolytic activity in response to corticosteroids, cellular production of plasminogen activator by both the mouse macrophage and human neutrophil is blocked by corticosteroids.…”
Section: Mechanisms Of Steroid-induced Vascular Damagementioning
confidence: 99%